PENGARUH PROFITABILITAS, CORPORATE SOCIAL RESPONSIBILITY, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Komang Fanny Krisnayanti Arta; I Gusti Ayu Ratih Permata Dewi; Ni Made Intan Priliandani (Jurnal MBE Manajemen Bisnis, Equilibrium, 2026)
This study aims to analyze the effect of profitability, Corporate Social Responsibility (CSR), and company size on firm value in the food and beverage subsector listed on the Indonesia Stock Exchange during 2022–2024. A quantitative explanatory approach was employed using secondary data from financial statements, annual reports, and sustainability reports. The sample consisted of 40 companies with a total of 120 observations selected through purposive sampling. Independent variables include profitability proxied by Return on Assets (ROA), CSR measured using the Corporate Social Responsibility Disclosure Index (CSRDI), and company size measured by the natural logarithm of total assets. Firm value, the dependent variable, is proxied by the Price Earning Ratio (PER). Panel data regression using the Fixed Effect Model, selected through Chow and Hausman tests, was applied. Results indicate that ROA, CSR, and company size simultaneously have a significant effect on PER. Partially, ROA and company size have a negative and significant effect, while CSR has no significant effect. These findings suggest that increases in profitability and company size do not necessarily raise market value, as investors consider long-term growth prospects and performance signals. Moreover, CSR disclosure, which is relatively uniform across companies, does not significantly differentiate investor perception. This study contributes theoretically to accounting research and practically to investment decision-making in the food and beverage subsector, especially during the post-pandemic recovery period.